2007
DOI: 10.1103/physrevd.75.105014
|View full text |Cite
|
Sign up to set email alerts
|

Goldstone bosons in presence of charge density

Abstract: We investigate spontaneous symmetry breaking in Lorentz-noninvariant theories. Our general discussion includes relativistic systems at finite density as well as intrinsically nonrelativistic systems. The main result of the paper is a direct proof that nonzero density of a non-Abelian charge in the ground state implies the existence of a Goldstone boson with nonlinear (typically, quadratic) dispersion law. We show that the Goldstone boson dispersion relation may in general be extracted from the current transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…[43] there are in fact only three Goldstone bosons, with two of them having a quadratic dispersion relation, in agreement with the Nielsen-Chadha theorem [44]. This abnormal number of Goldstone bosons can be related to the nonzero color charge [43,45,46], which arises in the 2SC phase as a consequence of the fact that only red and green quarks are paired. (In QCD, the 2SC phase is always color neutralized by the background gluon field [47].…”
Section: Meson and Diquark Spectra And Their Mixing In The 2sc Phasementioning
confidence: 64%
“…[43] there are in fact only three Goldstone bosons, with two of them having a quadratic dispersion relation, in agreement with the Nielsen-Chadha theorem [44]. This abnormal number of Goldstone bosons can be related to the nonzero color charge [43,45,46], which arises in the 2SC phase as a consequence of the fact that only red and green quarks are paired. (In QCD, the 2SC phase is always color neutralized by the background gluon field [47].…”
Section: Meson and Diquark Spectra And Their Mixing In The 2sc Phasementioning
confidence: 64%
“…In this Appendix, we clarify a confusion on discrete symmetries in the existing literature [74,75]. Contrary to the claim made in these references, we argue that type-B NGBs can appear without breaking any discrete symmetries such as the time-reversal symmetry (TRS).…”
Section: Approach 2: Gauging Hmentioning
confidence: 72%
“…In practical terms, the Ward identities for broken symmetries [15] establish the existence of massless modes generated by the broken currents. Moreover in the non-relativistic case, when commutators of broken generators have VEVs, it can be shown that some of these massless modes must have quadratic dispersion relations [16]. By carefully performing the procedure of obtaining the renormalized action of the holographic model, we will show that such Ward identities are exactly reproduced.…”
Section: Introductionmentioning
confidence: 91%
“…We thus deduce the presence of massless poles in all of these correlators. This additional Ward identity, which defines [3] type B Goldstone bosons, requires the dispersion relation to be quadratic [16], with the following argument.…”
Section: (35)mentioning
confidence: 99%